2020
DOI: 10.1002/jbio.202000289
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cartilage sub‐component distributions through the surface by Raman spectroscopy‐based multivariate analysis

Abstract: Articular cartilage posesses unique material properties due to a complex depth-dependent composition of sub-components. Raman spectroscopy has proven valuable in quantifying this composition through cartilage crosssections. However, cross-sectioning requires tissue destruction and is not practical in situ. In this work, Raman spectroscopybased multivariate curve resolution (MCR) was employed in porcine cartilage samples (n = 12) to measure collagen, glycosaminoglycan, and water distributions through the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Indeed, subtle molecular changes often cause detectable vibrational changes that can be detected by Raman analysis. In recent studies, Raman has been used either to more accurately quantify the distribution of cartilage subcomponents over its entire surface [25] or in some situations to establish the difference between different regions of the tissue over its entire depth the tissue surface [26].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subtle molecular changes often cause detectable vibrational changes that can be detected by Raman analysis. In recent studies, Raman has been used either to more accurately quantify the distribution of cartilage subcomponents over its entire surface [25] or in some situations to establish the difference between different regions of the tissue over its entire depth the tissue surface [26].…”
Section: Discussionmentioning
confidence: 99%
“…Because visual arthroscopic evaluation is highly subjective approach to assess cartilage degeneration, RS-based hydration status assessment may improve such clinical evaluation in near future. In fact, in a recent study, Mason et al [52] reported that it is possible to predict cartilage subcomponent distributions up to a depth of approximately 0.5 mm using multivariate curve resolution analysis of Raman spectra at "fingerprint region" (800-1800 cm À1 ) collected through the cartilage surface. This method could be also implemented for the high-wavenumber region to improve the sensitivity of water content measurement in the deeper zonal region of articular cartilage when the spectra are collected through the articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of articular cartilage are GAG and collagen [ 123 ], and changes in them can be used as indicators for the early diagnosis of OA. Mason et al [ 125 ] used Raman multivariate curve resolution (MCR) to analyze the cartilage surface, and their results showed that Raman MCR could accurately quantify the cartilage subcomponent distribution on the entire surface, with a depth of up to 0.5 mm. Jensen et al [ 126 ] collected Raman spectra from the cartilage tissue model and found that there were slight differences in the spectra of different tissue regions, which represented the orientation of collagen fibers, proving that polarized Raman spectroscopy can distinguish between collagen fiber orientations in the cartilage explant model system.…”
Section: Raman Spectroscopymentioning
confidence: 99%